Strategic Futures Studies and Entrepreneurial Resiliency: A Focus on Digital Technology Trends and Emerging Markets - Dana, Léo_Paul (2022)
Digital transformation and its unpredictable nature make future studies to be of paramount importance for dealing with a crisis and identifying market trends and opportunities existing in new markets. Moreover, future studies guarantee enterprises to develop accurate models toward their perspective and distinguish enterprises from their competitors. This study presents a strategic future study in entrepreneurial resiliency considering digital development trends in emerging markets. To do so, the researchers used the Delphi technique. The findings reveal that fifteen driving forces which panel experts suggested are effective in this regard. Artificial intelligence, data mining, environmental scanning, business circumstances prediction, and property research were of paramount importance among these forces. The paper concludes with some directions for future research and suggestions for policymakers and practitioners.